IL-33-induced ILC2 effector cytokine responses promote the expansion of red pulp macrophages - Irina R. Iten; Nikolaos D. Sidiropoulos; Lucas Onder; Aneta Jończy; Christoph S. N. Klose; Philippe Krebs; Katarzyna Mleczko-Sanecka; Burkhard Ludewig; Christoph Schneider; Manfred Kopf (Proceedings of the National Academy of Sciences, 2026)
Red pulp macrophages (RPMs) remove senescent erythrocytes from the circulation and recycle their iron for erythropoiesis. The development of RPMs is guided by signals from the microenvironment, which promote expansion and tissue adaptation through the induction of transcription factors, including Spi-C and PPARγ. Here, we show that infection with the nematode Nippostrongylus brasiliensis or treatment with IL-33 results in the accumulation of activated group 2 innate lymphocytes (ILC2s) in the spleen. ILC2s activated by IL-33 drive the expansion of RPMs by secretion of the effector cytokines IL-4/IL-13 and GM-CSF. By contrast, we show that IL-33 is dispensable for RPM development and function under homeostatic conditions. Overall, our work uncovers a previously unrecognized crosstalk between ILC2s and RPMs during type 2 immune responses.